Peningkatan Perilaku Hidup Bersih Dan Sehat (PHBS) Sebagai Intervensi Pencegahan Kejadian Stunting Di Rw 03 Desa Sirnagalih Kecamatan Tamansari Kabupaten Bogor Tahun 2024 - Zakiah, Lela; Awalia, Mutia; Putri, Ega; Nurhayati, Siti; Ardiani, Tiara; Nabila, Wanda (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
In our nation, stunting remains a serious health issue that has to be addressed. According to WHO data from 2020, Indonesia has the second-highest rate of stunted children under five in Southeast Asia, with a rate of 31.8%. The Community Midwifery Care Intervention Practice seeks to reduce stunting by educating and raising public knowledge of the use of Clean and Healthy Living Behavior (PHBS) as an intervention. With a sample size of thirty, this study employed the lecture technique with booklets and posters. Respondents completed questionnaires that were distributed as part of the data collection process. According to the research findings, there was a significant influence on promoting clean and healthy living behavior (PHBS) as an intervention to prevent stunting, as evidenced by the pretest value which showed that the greatest number of people with poor knowledge was 21 (70.0%), and the posttest results indicated that the greatest number of people with good knowledge was 27 (90.0%). The t value for this effect was 4.835. To sum up, there is an impact on raising awareness of Clean and Healthy Living Behavior (PHBS) as a stunting prevention strategy.